Association between use of heated tobacco products and long-term respiratory effects considering smoking history: internet-based cross-sectional study in Japan - Yuki Kimura; Minoru Sugita (BMC Public Health)
Abstract Background With the use of heated tobacco products (HTPs) becoming more widespread in Japan, interest in the health effects of HTP has grown. Since the majority of HTP users are former smokers, information about the user’s smoking history and health status before HTP use is needed when assessing the health effects of HTP use. The limited epidemiological studies available did not consistently consider this information adequately, therefore we conducted a cross-sectional study investigating the association between HTP use and respiratory chronic diseases and symptoms. Methods The questionnaires were sent to a research panel members in Japan via the Internet, and individuals who met the study criteria and were either current exclusive HTP users, current exclusive cigarette users or those had never used tobacco products were selected. Information about the participants’ smoking history and health status before they used HTPs was obtained. The effects of participant smoking history before HTP use and the impacts on outcomes upon switching to HTP were assessed using a logistic regression model. The odds ratio (OR) for current exclusive HTP users relative to never tobacco users was calculated. The OR was calculated under two scenarios, one in which the smoking history was ignored or one in which the smoking history was considered. Results Of the participants from whom responses to the questionnaires were obtained, 17,406 participants were included in the analysis. Almost all participating current exclusive HTP users had a history of long-term smoking (mean: 30.8 years), and the occurrence of outcomes both before and after the start using HTP was reported. The ORs, without adjustment and with adjustment for smoking history before HTP use were, 3.23 (95% CI: 1.37–7.61) and 1.85 (95% CI: 0.70–4.89) respectively in COPD, same as other outcomes. Conclusions These results suggest that smoking history before HTP using affects the occurrence of outcomes, and underscore the importance of considering smoking history when assessing the health effect of HTP use. Since the duration of HTP use is considerably shorter than that of cigarette use at present, further research, such as follow-up surveys assessing the long-term respiratory effects of HTP use, will be necessary.